A flexible analysis procedure for geometrical detection of spatial deformation - Setan, Halim (1997)
Methods for deformation monitoring are based on two-epoch analysis. During geometrical deformation detection, it is required to transform the results into a common datum, identify a set of stable points and localize the deformation. This paper describes a flexible analysis procedure that incorporates stability determination, congruency testing, S-transformations, localization and testing of spatial deformation. The procedure has been implemented into a computer program, DETECT. Two photogrammetric monitoring schemes were analysed using DETECT for identifying the significance of spatial deformation between epochs. The results confirmed the suitability of the procedure in practical applications.